2015
DOI: 10.1097/qco.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma prophylaxis in haematopoietic cell transplant recipients

Abstract: Universal prophylaxis with TMP/SMX in allo pre-HCTSP patients should be implemented by all transplant programmes. Preemptive treatment with routine blood PCR monitoring is an option if prophylaxis cannot be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
140
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(150 citation statements)
references
References 53 publications
8
140
0
2
Order By: Relevance
“…There are many case reports of toxoplasmosis in transplant recipients, including haematopoietic cell (Barcan et al, 2002), heart (Gajurel et al, 2015), liver (Hamza et al, 2015), and kidney (Petty et al, 2015) transplant patients. A previous study reported a higher prevalence of T. gondii infection in renal transplant recipients (Soltani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many case reports of toxoplasmosis in transplant recipients, including haematopoietic cell (Barcan et al, 2002), heart (Gajurel et al, 2015), liver (Hamza et al, 2015), and kidney (Petty et al, 2015) transplant patients. A previous study reported a higher prevalence of T. gondii infection in renal transplant recipients (Soltani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that danger of transplanting an infected organ into a seronegative recipient is greater than that of transplanting a non-infected organ into a seropositive recipient (Chehrazi-Raffle et al, 2015). Fatal toxoplasmosis has been reported in heart, liver and bone marrow, haematopoietic stem cell transplant recipients (Castagnini et al, 2007; Caner et al, 2008; Stajner et al, 2013; Gajurel et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…T. gondii sero-prevalence in the United States is approximately 10% [6]. While the most common cause of post-transplant toxoplasmosis is reactivation of latent infection, toxoplasmosis can rarely be transmitted from a donor (even if asymptomatic) to recipients [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…In allo-HCT patients, toxoplasmosis usually results from reactivation of a latent infection, instead of a primary infection [4,5]. The sero-prevalence of T. gondii in the United States is approximately 10%, and it is estimated that at least 800 allo-HCT patients are at risk for reactivation annually [6]. Post-transplant toxoplasmosis is more common in endemic countries [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation